Aerogel composite material for air purification and preparation method thereof

By preparing carbon aerogel and silica aerogel composites with modified pore size distribution, the problem of existing air purification materials with low purification efficiency of tobacco smoke is solved, and high-efficiency adsorption and large-capacity adsorption effects are achieved.

CN119236872APending Publication Date: 2025-01-03AUBERWIND ENVIRONMENTAL TECHNOLOGY (NANJING) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411564162.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing air purification materials have low purification efficiency and small adsorption capacity, so they cannot effectively remove various harmful components in tobacco smoke.

Method used

Carbon aerogel and silica aerogel composites are prepared by ultrasonic dispersion, reducing agent treatment, thiocyanate reaction, drying and thermal activation, etc., to form an aerogel composite with a modified pore size distribution. Improve adsorption efficiency and capacity.

Benefits of technology

The adsorption efficiency and adsorption capacity of tobacco smoke are significantly improved, especially the adsorption efficiency of nicotine and its derivatives, and the regeneration treatment of the material is achieved through secondary thermal activation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236872A_ABST
    Figure CN119236872A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of air purification, and discloses an aerogel composite material for air purification and a preparation method thereof.The preparation method comprises the following steps that carbon aerogel is pretreated with a copper salt solution, a reducing agent, an alkaline substance and thiocyanate; uniformly mixing the pretreated carbon aerogel, industrial silica sol, boric acid and a surfactant, and adding hydrofluoric acid to obtain wet gel; carrying out drying treatment on the wet gel to obtain dry gel; and carrying out segmented thermal activation on the dry gel, and carrying out modification treatment in a trimethylchlorosilane steam reactor to obtain the aerogel composite material. The carbon aerogel is used as an inner layer, the silicon dioxide aerogel is used as an outer layer, and the chemical composition and the structure of the composite material are regulated and controlled through physical and chemical methods, so that the adsorption efficiency and the adsorption capacity of the material on tobacco smoke are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of air purification, and in particular to an aerogel composite material for air purification and a preparation method thereof. Background Art

[0002] Tobacco smoke includes second-hand smoke and third-hand smoke. Its main components are nicotine and its derivatives, benzene substances, aldehydes, particulate matter, tar and other components. Long-term exposure to it will have serious adverse effects on the normal life activities of the human body.

[0003] At present, due to the large differences in the types, structures and properties of compounds contained in tobacco smoke, commonly used activated carbon adsorption materials are limited by raw materials and process methods, and have problems such as poor pore size adjustment ability, low adsorption efficiency and small adsorption capacity, and are not suitable for removing tobacco smoke from the air. Summary of the invention

[0004] The object of the present invention is to provide an aerogel composite material for air purification and a preparation method thereof, so as to solve the problem that the air purification material has low purification efficiency and small adsorption capacity for tobacco smoke.

[0005] To achieve the above object, the present invention provides the following technical solutions: The present invention discloses a method for preparing an aerogel composite material for air purification, which specifically comprises the following steps: Step S1: ultrasonically disperse the carbon aerogel and copper salt solution, then add a reducing agent and an alkaline substance and stir in a water bath, then add thiocyanate and continue stirring for 10 to 30 minutes, centrifuge after the end, wash the precipitate with anhydrous ethanol, and dry at normal pressure to obtain a pretreated carbon aerogel; Step S2: mixing the pretreated carbon aerogel, industrial silica sol, boric acid and surfactant, adding hydrofluoric acid, reacting, and obtaining a wet gel after the reaction is completed; Step S3: drying the wet gel to obtain a dry gel; Step S4: performing segmented thermal activation on the dry gel, and then placing it in a reactor containing trimethylchlorosilane vapor for modification treatment to obtain an aerogel composite material.

[0006] Preferably, in step S1, the copper salt solution is one of copper sulfate solution, copper chloride solution, and copper nitrate solution, and the concentration is 0.1 mol / L; the reducing agent is one of sodium sulfite and potassium sulfite; the alkaline substance is one of ammonia water, sodium hydroxide, and potassium hydroxide; and the thiocyanate is one of potassium thiocyanate and sodium thiocyanate.

[0007] Preferably, in step S1, the mass ratio of carbon aerogel, copper salt solution, reducing agent, alkaline substance and thiocyanate is (5-10): (100-1000): (1-12): (0.5-2): (2-20); the water bath stirring temperature is 30-50° C., and the time is 10-30 min.

[0008] Preferably, the mass percentage of industrial silica sol in step S2 is 10-30%; the surfactant is one of polyvinyl pyrrolidone, benzalkonium chloride and benzalkonium bromide.

[0009] Preferably, in step S2, the mass ratio of the pretreated carbon aerogel, industrial silica sol, boric acid, surfactant, and hydrofluoric acid is 1: (10-20): (0.1-1): (0.02-0.05): (0.5-2); and the reaction time is 5-10 h.

[0010] Preferably, the drying process in step S3 is freeze drying or supercritical drying.

[0011] Preferably, the stepwise thermal activation method in step S4 is: under nitrogen protection, keeping the temperature at 300-400°C for 2-3 hours, then heating to 450-550°C for 1-2 hours, and finally heating to 800-900°C for 1-2 hours.

[0012] Preferably, the concentration of trimethylchlorosilane vapor in step S4 is 0.1-1 g / m 3 ; The modification treatment time is 1~5min.

[0013] The present invention discloses an aerogel composite material for air purification, which is prepared by adopting the above-mentioned method for preparing an aerogel composite material for air purification.

[0014] Beneficial effects of the present invention: 1. The present invention uses carbon aerogel as the inner layer and silicon dioxide aerogel as the outer layer, and regulates the chemical composition and structure of the composite material through physical and chemical methods, thereby effectively improving the adsorption efficiency and adsorption capacity of the material for tobacco smoke.

[0015] 2. The present invention shrinks the pores of the carbon aerogel under the action of the surface energy of water molecules during the pretreatment drying process, shifts the pore size distribution of the carbon aerogel to the left, increases the proportion of micropores and mesopores in the carbon aerogel, and can effectively improve the adsorption efficiency of the composite material. In the subsequent thermal activation process, the copper compound in the pretreated carbon aerogel is thermally decomposed, and the formed copper is evenly distributed in the composite material, effectively improving the adsorption efficiency of the composite material for nicotine and its derivatives.

[0016] 3. During the thermal activation of the dry gel, boric acid undergoes a thermal decomposition reaction, and the generated gas expands the pore size of the silica aerogel, making the gas molecule passage from the outside to the inside of the composite material smoother, which can effectively improve the adsorption capacity of the composite material. In addition, the presence of boric oxide can effectively prevent the interference of water molecules during the modification process.

[0017] 4. The composite material prepared by the present invention can regenerate the adsorption saturated material through a secondary thermal activation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 A schematic diagram of a method for preparing an aerogel composite material for air purification according to the present invention; Figure 2 TEM image of the composite material of Example 1 of the present invention; Figure 3 The pore size distribution diagram of the composite material prepared in Example 1 of the present invention; Figure 4 Adsorption curves of tobacco smoke by the composite materials prepared in Example 1 and Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0020] like Figure 1 As shown, a method for preparing an aerogel composite material for air purification specifically comprises the following steps: Step S1: ultrasonically disperse the carbon aerogel and a copper salt solution with a concentration of 0.1 mol / L, then add a reducing agent and an alkaline substance, stir for 10 to 30 minutes at a water bath temperature of 30 to 50°C, then add thiocyanate and continue stirring for 10 to 30 minutes, centrifuge after completion, wash the precipitate with anhydrous ethanol, and dry at normal pressure to obtain a pretreated carbon aerogel; the copper salt solution is one of a copper sulfate solution, a copper chloride solution, and a copper nitrate solution; the reducing agent is one of sodium sulfite and potassium sulfite; the alkaline substance is one of ammonia water, sodium hydroxide, and potassium hydroxide; the thiocyanate is one of potassium thiocyanate and sodium thiocyanate; the mass ratio of carbon aerogel, copper salt solution, reducing agent, alkaline substance, and thiocyanate is (5 to 10): (100 to 1000): (1 to 12): (0.5 to 2): (2 to 20).

[0021] Step S2: mixing the pretreated carbon aerogel, 10-30% by mass of industrial silica sol, boric acid, and a surfactant, adding hydrofluoric acid, and reacting for 5-10 hours to obtain a wet gel; the surfactant is one of polyvinyl pyrrolidone, benzalkonium chloride, and benzalkonium bromide; the mass ratio of the pretreated carbon aerogel, industrial silica sol, boric acid, surfactant, and hydrofluoric acid is 1: (10-20): (0.1-1): (0.02-0.05): (0.5-2).

[0022] Step S3: drying the wet gel to obtain a dry gel; the drying process is one of freeze drying and supercritical drying.

[0023] Step S4: The dry gel is kept at 300-400°C for 2-3 hours under nitrogen protection, then heated to 450-550°C for 1-2 hours, and finally heated to 800-900°C for 1-2 hours, and then placed in a concentration of 0.1-1 g / m 3 The aerogel composite material is obtained by modifying the reactor with trimethylchlorosilane vapor for 1 to 5 minutes.

[0024] Embodiment 1: This embodiment specifically includes the following steps; Step S1: 5 g of carbon aerogel and 100 g of 0.1 mol / L copper sulfate solution were ultrasonically dispersed, and then 1 g of sodium sulfite and 0.5 g of ammonia water were added, and the water bath temperature was 30°C and stirred for 10 min. Then 2 g of potassium thiocyanate was added and stirred for 10 min. After the end, centrifugation was performed, and the precipitate was washed with anhydrous ethanol and dried at normal pressure to obtain the pretreated carbon aerogel.

[0025] Step S2: Add 0.5 g of hydrofluoric acid to 1 g of pretreated carbon aerogel, 10 g of 10% industrial silica sol, 0.1 g of boric acid, and 0.02 g of polyvinyl pyrrolidone, and react for 5 h to obtain a wet gel.

[0026] Step S3: freeze-drying the wet gel to obtain a dry gel.

[0027] Step S4: The dry gel was kept at 300°C for 2 h under nitrogen protection, then heated to 450°C for 1 h, and finally heated to 800°C for 1 h, and then placed in a 0.1 g / m 3 The aerogel composite material was obtained by modification treatment in a reactor with trimethylchlorosilane vapor for 1 min.

[0028] Figure 2 The TEM image of the composite material prepared in this example shows an obvious core-shell structure, with the inner layer being carbon aerogel and the outer layer being silicon dioxide aerogel. Figure 3This is the pore size distribution diagram of the composite material prepared in this example. It can be seen that the pore sizes of the composite material are mainly concentrated below 10 nm.

[0029] Embodiment 2: This embodiment specifically includes the following steps; Step S1: 10 g of carbon aerogel and 1000 g of 0.1 mol / L copper chloride solution were ultrasonically dispersed, and then 1 g of potassium sulfite and 2 g of potassium hydroxide were added, and the water bath temperature was 50°C and stirred for 30 min. Then 20 g of sodium thiocyanate was added and stirred for 30 min. After the end, centrifugation was performed, and the precipitate was washed with anhydrous ethanol and dried at normal pressure to obtain the pretreated carbon aerogel.

[0030] Step S2: 1 g of pretreated carbon aerogel, 20 g of 30% by mass industrial silica sol, 1 g of boric acid, and 0.05 g of benzalkonium chloride were mixed, 2 g of hydrofluoric acid was added, and the mixture was reacted for 10 h to obtain a wet gel.

[0031] Step S3: supercritically drying the wet gel to obtain a dry gel.

[0032] Step S4: The dry gel was kept at 400°C for 3 h under nitrogen protection, then heated to 550°C for 2 h, and finally heated to 900°C for 2 h, and then placed in a 1 g / m 3 The aerogel composite material was obtained by modification treatment in a reactor with trimethylchlorosilane vapor for 5 minutes.

[0033] Embodiment 3: This embodiment specifically includes the following steps; Step S1: 7 g of carbon aerogel and 500 g of 0.1 mol / L copper nitrate solution were ultrasonically dispersed, and then 6 g of potassium sulfite and 1 g of potassium hydroxide were added, and the water bath temperature was 50°C and stirred for 30 min, and then 12 g of potassium thiocyanate was added and continued to stir for 20 min. After completion, centrifugation was performed, and the precipitate was washed with anhydrous ethanol and dried at normal pressure to obtain the pretreated carbon aerogel.

[0034] Step S2: 1 g of pretreated carbon aerogel, 15 g of 20% by mass industrial silica sol, 0.5 g of boric acid, and 0.03 g of benzalkonium bromide were mixed, 1 g of hydrofluoric acid was added, and the mixture was reacted for 8 h to obtain a wet gel.

[0035] Step S3: freeze-drying the wet gel to obtain a dry gel.

[0036] Step S4: The dry gel was kept at 350°C for 2.5 h under nitrogen protection, then heated to 500°C for 1.5 h, and finally heated to 850°C for 1.5 h, and then placed in a 0.5 g / m 3 The aerogel composite material was obtained by modification treatment in a reactor with trimethylchlorosilane vapor for 3 minutes.

[0037] Embodiment 4: This embodiment specifically includes the following steps; Step S1: 8 g of carbon aerogel and 800 g of 0.1 mol / L copper sulfate solution were ultrasonically dispersed, and then 12 g of sodium sulfite and 1.5 g of sodium hydroxide were added, and the water bath temperature was 45 ° C. and stirred for 25 min, and then 15 g of sodium thiocyanate was added and continued to stir for 15 min. After completion, centrifugation was performed, and the precipitate was washed with anhydrous ethanol and dried at normal pressure to obtain the pretreated carbon aerogel.

[0038] Step S2: 1 g of pretreated carbon aerogel, 20 g of 25% by mass industrial silica sol, 0.6 g of boric acid, and 0.04 g of polyvinyl pyrrolidone were mixed, 1.5 g of hydrofluoric acid was added, and the mixture was reacted for 7 h to obtain a wet gel.

[0039] Step S3: freeze-drying the wet gel to obtain a dry gel.

[0040] Step S4: The dry gel was kept at 400°C for 2.5 h under nitrogen protection, then heated to 500°C for 1.5 h, and finally heated to 850°C for 1.5 h, and then placed in a 0.7 g / m 3 The aerogel composite material was obtained by modification treatment in a reactor with trimethylchlorosilane vapor for 4 minutes.

[0041] Embodiment 5: This embodiment specifically includes the following steps: Step S1: 10 g of carbon aerogel and 100 g of 0.1 mol / L copper sulfate solution were ultrasonically dispersed, and then 12 g of sodium sulfite and 2 g of sodium hydroxide were added, and the water bath temperature was 50°C and stirred for 10 min, and then 20 g of sodium thiocyanate was added and continued to stir for 30 min. After completion, centrifugation was performed, and the precipitate was washed with anhydrous ethanol and dried at normal pressure to obtain the pretreated carbon aerogel.

[0042] Step S2: 1 g of pretreated carbon aerogel, 10 g of 30% by mass industrial silica sol, 0.1 g of boric acid, and 0.02 g of polyvinyl pyrrolidone were mixed, and 0.5 g of hydrofluoric acid was added, and the mixture was reacted for 5 h to obtain a wet gel.

[0043] Step S3: freeze-drying the wet gel to obtain a dry gel.

[0044] Step S4: The dry gel was kept at 300°C for 2 h under nitrogen protection, then heated to 450°C for 1 h, and finally heated to 800°C for 1 h, and then placed in a 1 g / m 3 The aerogel composite material was obtained by modification treatment in a reactor with trimethylchlorosilane vapor for 5 minutes.

[0045] Comparative Example 1 The difference between this comparative example and Example 1 is that step S1 is not performed.

[0046] Comparative Example 2 The difference between this comparative example and Example 1 is that step S2 and step S3 are not performed.

[0047] Comparative Example 3 The difference between this comparative example and Example 1 is that step S4 is not performed.

[0048] Comparative Example 4 This comparative example uses commercial activated carbon as a blank control.

[0049] Referring to the test method for wood activated carbon in GB / T 12496.5-1999, tobacco smoke adsorption experiments were conducted on the materials of Examples 1-5 and Comparative Examples 1-4 under the same test conditions to test the time to reach equilibrium and the amount of nicotine adsorption.

[0050] The test results are shown in Table 1: Table 1 Summary of adsorption results

[0051] From Table 1 and combined Figure 4 It can be seen that compared with Comparative Example 4, Examples 1-4 have longer equilibrium time and larger adsorption amount, which is mainly due to the fact that the present invention uses carbon aerogel as the inner layer and silica aerogel as the outer layer, and regulates the chemical composition and structure of the composite material by physical and chemical methods, thereby effectively improving the adsorption efficiency and adsorption capacity of the material for tobacco smoke; compared with Comparative Examples 1-3, Examples 1-5 have longer equilibrium time and larger adsorption amount, which is mainly due to the fact that the present invention shrinks the pores of the carbon aerogel under the action of the surface energy of water molecules during the pretreatment drying process, thereby shifting the pore size distribution of the carbon aerogel to the left, increasing the proportion of micropores and mesopores in the carbon aerogel, and thus effectively improving the adsorption efficiency of the composite material. In the subsequent thermal activation process, the copper compound in the pretreated carbon aerogel is thermally decomposed, and the formed copper is evenly distributed in the composite material, effectively improving the adsorption efficiency of the composite material for nicotine and its derivatives. In addition, during the thermal activation of the dry gel, the boric acid undergoes a thermal decomposition reaction, and the generated gas expands the pore size of the silica aerogel, making the gas molecule pathway from the outside to the inside of the composite material smoother, which can effectively improve the adsorption capacity of the composite material. In addition, the presence of boron oxide can effectively prevent the interference of water molecules during the modification process.

[0052] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an aerogel composite material for air purification, characterized in that: The specific steps include: Step S1: ultrasonically disperse the carbon aerogel and copper salt solution, then add a reducing agent and an alkaline substance and stir in a water bath, then add thiocyanate and continue stirring for 10 to 30 minutes, centrifuge after the end, wash the precipitate with anhydrous ethanol, and dry at normal pressure to obtain a pretreated carbon aerogel; Step S2: mixing the pretreated carbon aerogel, industrial silica sol, boric acid and surfactant, adding hydrofluoric acid, reacting, and obtaining a wet gel after the reaction is completed; Step S3: drying the wet gel to obtain a dry gel; Step S4: performing segmented thermal activation on the dry gel, and then placing it in a reactor containing trimethylchlorosilane vapor for modification treatment to obtain an aerogel composite material.

2. The method for preparing an aerogel composite material for air purification according to claim 1, characterized in that: In step S1, the copper salt solution is one of copper sulfate solution, copper chloride solution, and copper nitrate solution, and the concentration is 0.1 mol / L; the reducing agent is one of sodium sulfite and potassium sulfite; the alkaline substance is one of ammonia water, sodium hydroxide, and potassium hydroxide; and the thiocyanate is one of potassium thiocyanate and sodium thiocyanate.

3. The method for preparing an aerogel composite material for air purification according to claim 1, characterized in that: In step S1, the mass ratio of carbon aerogel, copper salt solution, reducing agent, alkaline substance and thiocyanate is (5-10): (100-1000): (1-12): (0.5-2): (2-20).

4. The method for preparing an aerogel composite material for air purification according to claim 1, characterized in that: In step S1, the water bath stirring temperature is 30-50° C. and the stirring time is 10-30 min.

5. The method for preparing an aerogel composite material for air purification according to claim 1, characterized in that: In step S2, the mass percentage of industrial silica sol is 10-30%; the surfactant is one of polyvinyl pyrrolidone, benzalkonium chloride and benzalkonium bromide.

6. The method for preparing an aerogel composite material for air purification according to claim 1, characterized in that: In step S2, the mass ratio of the pretreated carbon aerogel, industrial silica sol, boric acid, surfactant, and hydrofluoric acid is 1: (10-20): (0.1-1): (0.02-0.05): (0.5-2); and the reaction time is 5-10 hours.

7. The method for preparing an aerogel composite material for air purification according to claim 1, characterized in that: The drying process in step S3 is one of freeze drying and supercritical drying.

8. The method for preparing an aerogel composite material for air purification according to claim 1, characterized in that: The stepwise thermal activation method in step S4 is: under nitrogen protection, keep the temperature at 300-400°C for 2-3 hours, then heat to 450-550°C and keep for 1-2 hours, and finally heat to 800-900°C and keep for 1-2 hours.

9. The method for preparing an aerogel composite material for air purification according to claim 1, characterized in that: The concentration of trimethylchlorosilane vapor in step S4 is 0.1-1 g / m 3 ; The modification treatment time is 1~5min.

10. An aerogel composite material for air purification, characterized in that: The aerogel composite material for air purification is prepared by the preparation method of the aerogel composite material for air purification as described in claims 1-9.